The Contribution of Arabic Language Learning in Forming Islamic Character from the Perspective of Islamic Religious Education - Dimas Wahyu Ramadhan; Dwi Aulia Putri (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the contribution of Arabic language learning to the formation of Islamic character among students from the perspective of Pendidikan Agama Islam using a literature review approach. The study is based on the analysis of various academic sources, including books, journal articles, and previous research. The findings indicate that Arabic language learning plays a significant role in enabling students to understand original Islamic texts, such as the Qur’an and Hadith, which contributes to the internalization of Islamic values including morality, ethics, and faith. Furthermore, the process of learning Arabic fosters discipline and perseverance, which are essential components of Islamic character. Therefore, the integration of Arabic language learning and Islamic education is an effective approach in developing a comprehensive Islamic personality.